2015
DOI: 10.1016/j.actamat.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thermal embrittlement in duplex stainless steels 2003 and 2205 for nuclear power applications

Abstract: Duplex stainless steels are desirable for use in power generation systems due to their attractive combination of strength, corrosion resistance, and cost. However, thermal embrittlement at intermediate homologous temperatures of ~475°C and below, limits upper service temperatures for many applications. New lean grade duplex alloys have improved thermal stability over standard grades and potentially increase the upper service temperature or the lifetime at a given temperature for this class of material. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…A number of studies showed that the impact property of DSSs decreased significantly with increasing thermal aging time, and the hardness of the ferrite in the DSSs increased significantly . The studies confirm further that the Cr‐rich, Fe‐rich, and G phases formed during a spinodal decomposition process impede the dislocations movement and harm the plastic deformation ability of the DSSs, resulting in an increase and a decrease for the hardness and impact property, respectively.…”
Section: Introductionmentioning
confidence: 68%
“…A number of studies showed that the impact property of DSSs decreased significantly with increasing thermal aging time, and the hardness of the ferrite in the DSSs increased significantly . The studies confirm further that the Cr‐rich, Fe‐rich, and G phases formed during a spinodal decomposition process impede the dislocations movement and harm the plastic deformation ability of the DSSs, resulting in an increase and a decrease for the hardness and impact property, respectively.…”
Section: Introductionmentioning
confidence: 68%
“…It is worth noting that the Cr-rich precipitate produced by spinodal decomposition and the magnetic martensite produced by cold working are usually cited with the same symbol (α') [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , but these are phases completely distinct. For this reason, in this paper, the Cr-rich precipitate produced by spinodal decomposition was called α 1 .…”
Section: Methodsmentioning
confidence: 99%
“…By using Reed and Schramm empirical formula, a SFE of ~ 63 mJ/m 2 is found for the AISI 317L 19 steel. Therefore, α'-martensite formation in this steel is expected to be ruled by reaction (5).…”
Section: Methodsmentioning
confidence: 99%
“…The grain refinement promoted by the duplex structure and the alloying elements provide higher mechanical strength than austenitic and ferritic grades such as AISI 304 and AISI430, respectively [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%